Neuromuscular and electromyographic responses to tailored plyometric training in elite heavyweight wrestlers - Khothier, G. K. (Modern Sport, 2025)
This study aimed to examine the impact of a specialized plyometric training program on neuromuscular and EMG responses in elite heavyweight wrestlers. The focus was on exploring changes in muscle activation patterns, contraction velocity, and motor latencies following a tailored training protocol. A quasi-experimental design was used, with 12 elite heavyweight male wrestlers. Electromyographic data were collected from the vastus lateralis, biceps femoris, and gastrocnemius muscles. Maximum voluntary contraction (MVC) and contraction velocity were assessed using an isokinetic dynamometer. A plyometric training program was conducted three times per week for six weeks, including exercises such as depth jumps, hurdle hops, and lateral bounds. Significant improvements were observed in EMG amplitude, with the vastus lateralis showing a large effect size (Cohen`s d = 1.45). Contraction velocity also improved significantly, with mean increases of 15.4°/s (60°/s) and 25.8°/s (180°/s). Additionally, motor reaction time decreased by 23.2 ms (Cohen`s d = 1.42). These results indicate significant neuromuscular adaptations following plyometric training. The study demonstrated that a personalized plyometric training protocol significantly enhances neuromuscular performance in elite heavyweight wrestlers. These improvements in muscle activation, contraction velocity, and motor reaction time suggest the effectiveness of plyometric training in combat sports, particularly for athletes with higher body mass. Future research should explore long-term effects and applications for injury prevention in combat sports.